Breastfeeding Experiences of Taiwanese Mothers of Infants with Breastfeeding or Breast Milk Jaundice in Certified Baby-Friendly Hospitals - Kuei-Hui Chu; Shuh-Jen Sheu; Mei-Hwa Hsu; Jillian Liao; Li-Yin Chien (Elsevier, 2019)
Purpose: The purpose was to explore the breastfeeding experiences of mothers of infants with breastfeeding or breast milk jaundice. Methods: In-depth qualitative interviews and content analysis were conducted with nine mothers of newborns with breastfeeding and/or breast milk jaundice who breastfed their babies during the first year postpartum. Results: Mothers' experiences can be described in four phases and six themes. (1) Prenatal stage: build breastfeeding belief, i.e., breastfeeding is best and a natural behavior, without awareness of neonatal jaundice; (2) stage after neonatal jaundice started to appear: include two themes, questioning beliefs in breastfeeding and happiness in being a mother. Mothers lacked knowledge and ignored the threat of neonatal jaundice, mainly focused on their physical discomforts and worried about insufficient breast milk; they also felt an intimate mother-infant bond through breastfeeding; (3) stage when newborns had confirmed diagnosis of breastfeeding or breast milk jaundice that required medical attention: include two themes, diagnosis of breastfeeding or breast milk jaundice and phototherapy caused negative emotions and regaining original beliefs about breastfeeding. They struggled through emotional swings and inconsistent advices about whether phototherapy and formula supplementation are needed. Then, they decided breastfeeding or breast milk jaundice is only temporary and retrieved initial beliefs of breastfeeding. (4) Stage after neonatal jaundice faded and mothers continued breastfeeding: insisting and adapting. Conclusion: Breastfeeding mothers were unaware of neonatal jaundice until medical attention was required; they experienced physical and mental distress and gradually learned to manage jaundice while insisting on breastfeeding through their breastfeeding beliefs and happiness in being mothers. Keywords: anxiety, breast feeding, jaundice, neonatal, qualitative research